Effect of airborne pathogen transmission released by an assailant in a mosque using CFD simulation. - Mat, Mohamad Nur Hidayat (Penerbit UTHM, 2023)
This study investigated the aerosol particle spreading characteristic under transient state at different location released by an assailant inside a mosque. Particles deposited at receivers were used to determine the virus reproductive number (Ro) over time. The spreading during coughing process was validated with previous literature review using Computational Fluid Dynamics (CFD) simulation study. Mesh sensitivity study was done on the model to get better accuracy results and optimum computational load. The model involved internal space of the mosque and 160 prayers during the congregation prayers. It was discovered that, the particle spreading characteristics was found to be influenced mostly by the velocity distribution and velocity vector inside the mosque. This is due to force flow generated by fan and air conditioner air flow. Particles size less than 10 μm were the most deposited on the wall and ceiling. The particles greater than 30 μm deposited on the ground and the prayers body. The location of assailant at the center was found to cause the most infection among the prayers which was 52% of the total prayer with the Ro of 0.83. The assailant at top right and bottom right produced high Ro of 0.73 and 0.6 while top left produced the lowest which was 0.32. The existence of partition was found to reduce the particle spreading from the assailant at bottom left.